Działania izb przemysłowo-handlowych na rzecz rozwoju innowacyjności polskich przedsiębiorstw - WALKOWIAK, Katarzyna (Przegląd Politologiczny, 2018)
In a knowledge-based economy innovativeness is among the most significant factors that are decisive for the competitiveness of modern businesses. EU member states undertake numerous activities to support the innovativeness of their businesses and to reduce the distance between them and the global leaders of innovativeness. In Poland only a small proportion of businesses run innovative activities and the level of innovativeness of the economy significantly differs from that of the majority of EU states. Stimulating an enterprise’s innovative potential is significantly influenced by cooperation and connections with the institutions of the business environment. The institutions supporting the innovative activity of businesses in Poland are not fit to meet their needs. At the same time the civil factor, namely the entrepreneurs, is not taken advantage of. Their role in business life can be strengthened by the chambers of commerce and industry – the institutions of public law that represent all entrepreneurs and which are competent to participate in the shaping and implementation of policies to promote the innovativeness of the state and its regions.